PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGASI (GI) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SDN 003 PASIR BONGKAL KECAMATAN SEI LALA - Sriani '; Hendri Marhadi; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study was motivated by the fact their most Class V students of SDN 003 Pasir Bongkal Kecamatan Sei Lala did not master the subject matter IPS has learned. The problem of this research is "Does the implementation of cooperative learning model investigation group (GI) can improve learning outcomes IPS Student Class V SDN 003 Pasir Bongkal Kecamatan Sei Lala?". This study aims to improve learning outcomes IPS at Class V SDN 003 Pasir Bongkal Kecamatan Sei Lala through the implementation of cooperative learning model investigation group (GI). This study was conducted in April 2016. The research was Classroom Action Research (PTK) with two cycles. Subjects were 20 people consists of 11 girls and 9 boys. Based on the results of the study are improvement of learning outcomes from a base score of 61.5 increase at UH I to 71.5 with an increase of 16.3%. At UH II increased to 78.25 with an increase of 9.4%. Overall 25.7% increase in learning outcomes. Then of completeness individual and classical, in the first cycle the number of students who pass as many as 13 people by 65% and incomplete 7 by 35%, while in the second cycle the number of students who completed 18 of 90%, while the incomplete 2 by 10%. Then the increased activity of teachers at the meeting 1siklus I by 54.2% in the second meeting of 58.3%. In the second cycle teachers' meeting 1 activity by 70.8% in the second meeting of the second cycle by 75%. While the activities of students at the meeting 1siklus I by 50% in the second meeting of 58.3%. In the second cycle 1 meeting student activity by 75% in the second meeting of the second cycle by 75%. Keywords:  Cooperative Learning Model Group Investigation (GI), Learning Outcomes, IPS